Potential factors associated with knee pain in cyclists: a systematic review - Bini RR; Flores Bini A (Dove Medical Press, 2018)
Rodrigo Rico Bini, Alice Flores Bini La Trobe Rural Health School, La Trobe University, Flora Hill Campus, Bendigo, VIC, Australia Abstract: The potential factors associated with overuse injuries and pain in cyclists that are supported by evidence remain unclear. Our study aimed at assessing, using a systematic search of the most updated evidence, the main factors related to overuse knee-related pain and/or injuries in cyclists. The search assessed any potential mechanism related to knee pain or injury that could be used in the clinical practice. Databases were searched (i.e., PubMed, Scopus, Web of Science, and EBSCO). Studies were included if they presented results from original studies. They had to include, preferably but not limited to, recreational and/or competitive cyclists with or without knee pain. Quality of articles was assessed. Eleven articles were deemed eligible for full text appraisal. Studies involved generally the assessment of biomechanical outcomes associated with knee pain in cyclists. Overall, studies showed that cyclists with knee pain present larger knee adduction and larger ankle dorsiflexion and differences in activation for hamstrings and quadriceps muscles. Unclear results were observed for knee moments and no differences were observed for knee flexion angle, tibiofemoral and patellofemoral forces. It is important to state that varied types of knee pain were mixed in most studies, with 2 focused on anterior-related pain. Cyclists with overuse-related pain or injuries on their knees presented an increased medial projection of their knees and an altered activation of the Vastus Medialis and Vastus Lateralis muscles. However, this limited evidence is based on retrospective studies comparing cyclists with and without pain, which limits the conclusion on how cyclists develop knee pain and what are the main options for treatment of knee pain. Keywords: injury, cycling, overuse, biomechanics